Association Between Long-Term Cognitive Decline in Vietnam Veterans With TBI and Caregiver Attachment Style. Issue 1 (January 2015) - Guevara, Andrea Brioschi; Démonet, Jean-François; Polejaeva, Elena; Knutson, Kristine M.; Wassermann, Eric M.; Krueger, Frank; Grafman, Jordan
<x xml:space="preserve">Abstract</x> Objective: To examine whether a caregiver's attachment style is associated with patient cognitive trajectory after traumatic brain injury (TBI). Setting: National Institute of Neurological Disorders and Stroke, National Institutes of Health, Bethesda, Maryland. Participants: Forty Vietnam War veterans with TBI and their caregivers. Main Outcome Measure: Cognitive performance, measured by the Armed Forces Qualification Test percentile score, completed at 2 time points: preinjury and 40 years postinjury. Design: On the basis of caregivers' attachment style (secure, fearful, preoccupied, dismissing), participants with TBI were grouped into a high or low group. To examine the association between cognitive trajectory of participants with TBI and caregivers' attachment style, we ran four 2 × 2 analysis of covariance on cognitive performances. Results: After controlling for other factors, cognitive decline was more pronounced in participants with TBI with a high fearful caregiver than among those with a low fearful caregiver. Other attachment styles were not associated with decline. Conclusion and Implication: Caregiver fearful attachment style is associated with a significant decline in cognitive status after TBI. We interpret this result in the context of the neural plasticity and cognitive reserve literatures. Finally, we discuss its impact on patient demand for healthcare services and potential interventions.